CHARACTERISTICS OF THE MANAGEMENT OF A COMORBID PATIENT. LOOKING AT THE PROBLEM FROM THE EYES OF A FAMILY DOCTOR - Вовк К.В.; Власенко О.О.; Шерстюк Л.Л.; Шумова Н.В.; Кратенко Г.С.; Резніченко О.Г. (World Science, 2023)
In the realities of today, family doctors are increasingly faced with comorbid patients. Moreover, with an increase in the life expectancy of people, this problem becomes large and infinitely diverse. Comorbidity can reduce patient adherence to treatment, including due to the use of multicomponent therapy regimens, which, in turn, leads to a decrease in the effectiveness of the treatment. In this regard, there is a need for individual selection of therapeutic regimens with minimal drug interactions. This imposes certain conditions on the family doctor in terms of continuous improvement in the study of the latest protocols and treatment regimens of all therapeutic specialties. This article presents a clinical case of a comorbid patient with pathology of the cardiovascular and digestive systems. The choice of a diagnostic and treatment algorithm was based on modern Ukrainian and foreign recommendations. Emphasis is placed on the stratification of both cardiac and gastroenterological risk factors, and the strategy for choosing proton pump inhibitors depending on the clinical dynamics. On a specific clinical example, an algorithm for choosing the diagnosis and treatment of a comorbid patient under different scenarios of pathology development, taking into account existing approaches and recommendations, is demonstrated. It has been shown that the problem of comorbidity leaves many questions for practitioners and often requires broad knowledge from the attending physician, and sometimes a multidisciplinary approach.